High-strength water-resistant corrugated paper and application thereof in waterproof carton
By comprehensively treating the corrugated core paper with impregnation liquid and coating, and using modified silica sol, boron quantum dot modified titanium dioxide and modified hydroxyethyl cellulose, the problems of low edge compression strength, poor flame retardant performance and high water absorption are solved, and the performance of corrugated paper is significantly improved.
Patent Information
- Application Number
- CN202510035389.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-09
AI Technical Summary
The existing corrugated paper has low edge pressure strength, poor flame retardant performance, and high water absorption, which seriously affects its actual use.
By using impregnation liquid and coating, modified silica sol and boron quantum dot modified titanium dioxide are added to the impregnation liquid, and modified hydroxyethyl cellulose is added to the coating to improve the edge pressure strength, oxygen index and reduce water absorption of the corrugated paper.
It significantly increases the edge pressure strength of corrugated paper, improves the oxygen index, and effectively reduces water absorption, improving the overall performance of corrugated paper.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of corrugated paper, and in particular relates to high-strength water-resistant corrugated paper and application thereof in waterproof cartons. Background Art
[0002] Corrugated paper is a commonly used packaging material, consisting of one or more layers of corrugated inner core and one or two layers of flat outer paper. It has become a very commonly used paper packaging material due to its low gram weight, low cost, high strength, excellent cushioning performance and environmental friendliness. Since the birth of corrugated paper, there have been many studies on its various properties, including the influence of corrugated paper materials, structures, manufacturing processes, external loads and climate environment on its static and dynamic properties. These studies have enabled people to have a clear understanding of most of the properties of corrugated paper, laying a good foundation for its application in packaging and other fields.
[0003] A Chinese patent (publication number CN117661366A) discloses a preparation process of a high-strength water-resistant composite corrugated paper. The invention uses amino-terminated hyperbranched fluorinated polyamide-ester as a curing agent, contains hydrophobic benzene rings and trifluoromethyl groups, can improve the hydrophobicity of epoxy resin sizing agents, reduce water absorption, thereby forming a hydrophobic coating on the surface of corrugated paper, and improving the water resistance and waterproof performance of corrugated paper. The amino-terminated hyperbranched fluorinated polyamide-ester has a hyperbranched molecular chain structure, forms a three-dimensional cross-linked network in epoxy resin, plays a good strengthening and toughening effect on epoxy resin, improves the impact strength and bending strength of epoxy resin, and is conducive to improving the ring compression index and ring compression strength of corrugated paper. However, the patent does not solve the problems of low side compression strength, poor flame retardant performance, and high water absorption of corrugated paper in the prior art, which seriously affects its actual use.
[0004] Therefore, there is an urgent need for a high-strength and water-resistant corrugated paper. The corrugated core paper is comprehensively treated with an impregnating liquid and a coating, and the key components of the impregnating liquid and the coating are modified to increase the edge compression strength of the corrugated paper, improve the oxygen index, and effectively reduce the water absorption. Summary of the invention
[0005] The purpose of the present invention is to provide a high-strength and water-resistant corrugated paper and its application in waterproof cartons. The corrugated core paper is comprehensively treated by using an impregnation liquid and a coating, and modified silica sol and boron quantum dot-modified titanium dioxide are used in the impregnation liquid. At the same time, the hydroxyethyl cellulose in the coating is modified to prepare a high-strength and water-resistant corrugated paper, which significantly increases the edge compression strength, improves the oxygen index, and effectively reduces the water absorption.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] The first aspect of the present invention provides a high-strength and water-resistant corrugated paper, the high-strength and water-resistant corrugated paper comprising a corrugated core paper and a functional coating coated on the surface of the corrugated core paper, wherein the corrugated core paper is treated by impregnation and modification with an impregnation liquid;
[0008] The corrugated paper is made by the following steps:
[0009] Step S1: in parts by weight, 10 to 20 parts of ethyl orthosilicate, 6 to 10 parts of paraffin, 20 to 24 parts of anhydrous ethanol and 20 to 24 parts of deionized water are mixed uniformly, stirred at 46 to 48° C. for 20 to 30 minutes, the pH is adjusted to 4.2 to 4.8 with hydrochloric acid and stirred for 2 to 4 hours, then 20 to 30 parts of a magnesium chloride solution with a molar concentration of 0.1 to 0.3 mol / L is added, stirred at 54 to 60° C. for 4 to 6 hours, and then ammonia water is added dropwise to adjust the pH to 7.4 to 7.8 and stirred for 1 to 2 hours to obtain a modified silica sol;
[0010] Step S2: adding 4 to 6 parts of sodium hydroxide to 90 to 100 parts of the modified silica sol by weight, stirring at 70 to 80° C. for 50 to 60 minutes, then adding 4 to 6 parts of methyl cellulose and 1 to 3 parts of titanium dioxide and continuing to stir for 30 to 40 minutes to obtain an impregnation solution;
[0011] Step S3: immersing the corrugated core paper in the impregnation liquid at 50-60° C. for 10-20 seconds, and then drying it in a constant temperature blast drying oven at 56-60° C. for 50-60 minutes to obtain the impregnated corrugated core paper;
[0012] Step S4: coating the impregnated corrugated paper with a coating, and after the coating is completed, first standing at room temperature for 10 to 20 minutes, then curing at 100 to 104° C. for 70 to 80 minutes, and finally processing with a corrugated roller to obtain high-strength and water-resistant corrugated paper.
[0013] The paraffin in the modified silica sol can form a protective film on the surface. When encountering flames, the paraffin will melt and cover the paper, playing a role of physical isolation, thereby delaying the combustion process; at the same time, magnesium hydroxide grows in situ on the surface of silica. Magnesium hydroxide can decompose into water vapor and magnesium oxide at high temperatures and absorb a large amount of heat, while releasing non-flammable water vapor, diluting the concentration of combustible gases, reducing flame temperature, and increasing the oxygen index of corrugated paper.
[0014] As a preferred solution, the methyl cellulose is carboxymethyl cellulose and hydroxypropyl methyl cellulose; the mass ratio of the carboxymethyl cellulose to the hydroxypropyl methyl cellulose is (1-2):1.
[0015] By controlling the mass ratio of carboxymethyl cellulose and hydroxypropyl methyl cellulose and ensuring the appropriate dosage of the two, the edge compression strength of corrugated paper is increased, the oxygen index is improved, and the water absorption is effectively reduced by virtue of a good compounding effect.
[0016] As a preferred solution, the titanium dioxide is boron quantum dot-modified titanium dioxide; the preparation method of the boron quantum dot-modified titanium dioxide comprises: by weight, 60 to 80 parts of anhydrous ethanol, 20 to 40 parts of deionized water, 2 to 4 parts of boron quantum dots and 8 to 10 parts of hydrochloric acid solution with a mass concentration of 20 to 30% are mixed and stirred for 10 to 20 minutes to obtain liquid A; 60 to 80 parts of tetrabutyl titanate are added to 90 to 100 parts of anhydrous ethanol and stirred for 20 to 30 minutes, and then the mass concentration is 20 to 30%. The pH value is adjusted to 3.2-3.6 with 30% hydrochloric acid solution, and stirred for 15-30 minutes to obtain liquid B; 80-100 parts of the liquid A are added to 100-120 parts of the liquid B and stirred for 40-60 minutes, and then 20-40 parts of deionized water are added and stirred for 2-4 hours to form a gel, which is allowed to stand at room temperature for 10-12 hours, and then dried at 70-80°C for 20-22 hours, transferred to a tubular furnace and calcined at 480-500°C for 2-4 hours, and cooled to room temperature to obtain boron quantum dot-modified titanium dioxide.
[0017] As a preferred scheme, the preparation method of boron quantum dots includes: adding 2 to 4 parts of ammonium pentaborate and 1 to 2 parts of boric acid to 20 to 25 parts of deionized water by weight, stirring for 1 to 2 hours, placing in an argon atmosphere for hydrothermal reaction, cooling to room temperature after the reaction is completed, adding 1 to 2 parts of hydrazine hydrate and stirring for 1 to 2 hours, then centrifuging to obtain a supernatant, freeze-drying, and obtaining boron quantum dots.
[0018] As a preferred solution, the reaction temperature of the hydrothermal reaction is 180-190° C., and the reaction time is 10-12 h.
[0019] The boron quantum dots in boron quantum dot-modified titanium dioxide can form strong physical adsorption with corrugated paper fibers, improve the bonding force between fibers, and thus enhance the stability of the overall structure; titanium dioxide has high hardness and good weather resistance, and can fill the gaps between paper fibers to provide additional structural support and enhance the edge compression strength of corrugated paper.
[0020] As a preferred solution, the preparation method of the coating includes: mixing 4 to 6 parts of acetic acid and 60 to 70 parts of deionized water in parts by weight, and then adding 90 to 100 parts of polyurethane, 1 to 3 parts of methanol and 4 to 8 parts of hydroxyethyl cellulose and stirring for 4 to 6 hours to obtain the coating.
[0021] As a preferred solution, the hydroxyethyl cellulose is modified hydroxyethyl cellulose; the preparation method of the modified hydroxyethyl cellulose comprises: adding 20 to 24 parts of hydroxyethyl cellulose to 100 to 110 parts of deionized water by weight, stirring for 1 to 3 hours under a nitrogen atmosphere, adding 6 to 8 parts of ammonium cerium nitrate and 10 to 14 parts of [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl)ammonium hydroxide at 36 to 40° C., adjusting the pH to 7.2 to 7.4, reacting for 4 to 6 hours, and precipitating with acetone after the reaction is completed. Separate to obtain a precipitate; add 36 to 40 parts of 2-acrylamido-2-methylpropanesulfonic acid and 10 to 14 parts of sodium chloride to 200 to 220 parts of deionized water and stir for 30 to 40 minutes, then add 40 to 45 parts of dimethyldiallylammonium chloride and 20 to 30 parts of the above precipitate, stir for 1 to 3 hours to obtain a mixed solution, transfer the mixed solution to a reaction kettle, add 2 to 4 parts of potassium persulfate at 80 to 84° C. under nitrogen atmosphere protection, react for 6 to 8 hours, cool to room temperature after the reaction is completed, dry, and crush to obtain modified hydroxyethyl cellulose.
[0022] As a preferred solution, the viscosity of the hydroxyethyl cellulose is 800-1200 mPa.s.
[0023] Modified hydroxyethyl cellulose contains zwitterionic polymers, which can reduce the capillary effect inside the corrugated paper and inhibit the absorption of moisture by changing the microstructure of the corrugated paper surface. At the same time, the modified hydroxyethyl cellulose and polyurethane can work together to form a hydrophobic barrier on the surface of the corrugated paper, effectively reducing the water absorption of the paper.
[0024] As a preferred solution, the coating amount in the coating process is 40 to 50 g / m 2 .
[0025] The second aspect of the present invention provides a use of the high-strength water-resistant corrugated paper as described in the first aspect in a waterproof carton.
[0026] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0027] 1. The present invention first introduces modified silica sol and boron quantum dot modified titanium dioxide through an impregnation liquid, and then introduces modified hydroxyethyl cellulose through a coating, wherein the zwitterionic polymer of the modified hydroxyethyl cellulose can produce an adsorption effect with the modified silica sol and boron quantum dot modified titanium dioxide to construct a dense network structure, thereby improving the edge compression strength of the corrugated paper and reducing its water absorption.
[0028] 2. The magnesium hydroxide in the modified silica sol of the present invention can absorb a large amount of heat and release non-flammable water vapor at high temperature, and the silicon element can promote the formation of a dense carbon layer on the surface of the material to improve the fire resistance; the boron element in the boron quantum dot modified titanium dioxide will form a stable glass-like film covering the surface of the material at high temperature, effectively isolating oxygen and heat; the nitrogen element in the modified hydroxyethyl cellulose can react with the free radicals generated during the combustion process, thereby blocking the chain reaction and slowing down the combustion process; through the synergistic effect of multiple elements of magnesium-silicon-boron-nitrogen, the oxygen index of corrugated paper is significantly improved.
[0029] 3. The paraffin in the modified silica sol of the present invention can form a protective film on the surface. When encountering flames, the paraffin will melt and cover the paper, playing a role of physical isolation, thereby delaying the combustion process; at the same time, magnesium hydroxide grows in situ on the surface of the silica, and the magnesium hydroxide can be decomposed into water vapor and magnesium oxide at high temperature and absorb a large amount of heat, while releasing non-flammable water vapor, diluting the concentration of combustible gas, reducing the flame temperature, and improving the oxygen index of the corrugated paper.
[0030] 4. The boron quantum dots in the boron quantum dot-modified titanium dioxide of the present invention can form strong physical adsorption with the corrugated paper fibers, improve the bonding force between the fibers, and thus enhance the stability of the overall structure; titanium dioxide has high hardness and good weather resistance, and can be filled into the gaps between paper fibers to provide additional structural support, thereby improving the edge compression strength of corrugated paper through the combined action of boron quantum dots and titanium dioxide.
[0031] 5. The modified hydroxyethyl cellulose of the present invention contains zwitterionic polymers, which can reduce the capillary effect inside the corrugated paper and inhibit the absorption of water by changing the microstructure of the surface of the corrugated paper. At the same time, the modified hydroxyethyl cellulose and the polyurethane can work together to form a hydrophobic barrier on the surface of the corrugated paper, effectively reducing the water absorption of the paper. DETAILED DESCRIPTION
[0032] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] The sources of some components in the embodiments and comparative examples are as follows:
[0034] Corrugated core paper, purchased from Lee & Man Paper Co., Ltd.;
[0035] Commercially available silica sol, product number sy07, was purchased from Qingdao Shuoyuan Silica Gel Technology Co., Ltd.;
[0036] Sodium hydroxide, CAS No. 1310-73-2, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0037] Carboxymethyl cellulose, CAS No. 9004-32-4, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0038] Hydroxypropyl methylcellulose, CAS No. 9004-65-3, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0039] Titanium dioxide, CAS No. 13463-67-7, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;
[0040] Polyurethane, model AH-1610, purchased from Anhui Dawei Huatai New Material Technology Co., Ltd.;
[0041] Hydroxyethyl cellulose I, product number H104791, viscosity 1100 mPa.s, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0042] Hydroxyethyl cellulose II, product number H104786, viscosity 200 mPa.s, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0043] Hydroxyethyl cellulose III, product number H104788, viscosity 4000 mPa.s, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0044] Ethyl orthosilicate, CAS No. 78-10-4, Shanghai Aladdin Biochemical Technology Co., Ltd.
[0045] Paraffin wax, product number 4100511, was purchased from Shandong Yousuo Chemical Technology Co., Ltd.;
[0046] Magnesium chloride, CAS No. 7786-30-3, purchased from Shanghai Jizhi Biochemical Technology Co., Ltd.;
[0047] Ammonium pentaborate, CAS No. 12007-89-5, purchased from Merck Chemical Co., Ltd.;
[0048] Boric acid, CAS No. 10043-35-3, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0049] Hydrazine hydrate, CAS No. 7803-57-8, purchased from Sigma-Aldrich (Shanghai) Trading Co., Ltd.;
[0050] Tetrabutyl titanate, CAS No. 5593-70-4, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;
[0051] Cerium ammonium nitrate, product number C3654, was purchased from Sigma-Aldrich (Shanghai) Trading Co., Ltd.;
[0052] [2-(Methacryloyloxy)ethyl]dimethyl-(3-sulfonatepropyl)ammonium hydroxide, CAS No. 3637-26-1, purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0053] 2-Acrylamido-2-methylpropanesulfonic acid, CAS No. 15214-89-8, purchased from Shanghai Huayuan Century Trading Co., Ltd.;
[0054] Sodium chloride, CAS No. 7647-14-5, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0055] Dimethyldiallylammonium chloride, CAS No. 7398-69-8, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0056] Potassium persulfate, CAS No. 7727-21-1, was purchased from Sinopharm Chemical Reagent Co., Ltd.
[0057] Example 1
[0058] This embodiment provides a high-strength and water-resistant corrugated paper, which includes a corrugated core paper and a functional coating coated on the surface of the corrugated core paper, wherein the corrugated core paper is treated by impregnation with an impregnation liquid for modification;
[0059] The corrugated paper is made by the following steps:
[0060] Preparation of boron quantum dot-modified titanium dioxide: (1) In parts by weight, 4 parts of ammonium pentaborate and 2 parts of boric acid were added to 25 parts of deionized water and stirred for 2 hours. The mixture was placed in an argon atmosphere for hydrothermal reaction (reaction temperature was 190°C and reaction time was 10 hours). After the reaction was completed, the mixture was cooled to room temperature, 2 parts of hydrazine hydrate were added and stirred for 2 hours, and then the supernatant was obtained by centrifugation and freeze-dried to obtain boron quantum dots. (2) In parts by weight, 80 parts of anhydrous ethanol, 40 parts of deionized water, 4 parts of boron quantum dots and 10 parts of 20% hydrochloric acid solution were mixed and stirred for 20 minutes to obtain liquid A; 80 parts of tetrabutyl titanate were added to 100 parts of anhydrous ethanol and stirred for 30 minutes, and then the pH was adjusted to 3.6 with 20% hydrochloric acid solution and stirred for 30 minutes to obtain liquid B; 100 parts of the liquid A were added to 120 parts of the liquid B and stirred for 60 minutes, and then 40 parts of deionized water were added and stirred for 4 hours to form a gel, which was allowed to stand at room temperature for 12 hours, and then dried at 80°C for 20 hours, transferred to a tubular furnace and calcined at 500°C for 2 hours, and cooled to room temperature to obtain boron quantum dot-modified titanium dioxide.
[0061] Preparation of coating: (1) In parts by weight, 24 parts of hydroxyethyl cellulose I (viscosity of 1100 mPa.s) are added to 110 parts of deionized water, stirred for 3 hours under a nitrogen atmosphere, 8 parts of cerium ammonium nitrate and 14 parts of [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl)ammonium hydroxide are added at 40°C, the pH is adjusted to 7.4, and the reaction is carried out for 6 hours. After the reaction is completed, precipitation and separation are carried out with acetone to obtain a precipitate; 40 parts of 2-acrylamido-2-methylpropanesulfonic acid and 14 parts of sodium chloride are added to 220 parts of deionized water and stirred for 40 minutes, and then 45 parts of dimethyldiallylammonium chloride and 30 parts of the above precipitate are added and stirred for 3 hours to obtain a mixed solution, which is transferred to a reactor, and 4 parts of potassium persulfate are added at 84°C under a nitrogen atmosphere for reaction for 6 hours. After the reaction is completed, the mixture is cooled to room temperature, dried, and crushed to obtain modified hydroxyethyl cellulose. (2) By weight, 6 parts of acetic acid and 70 parts of deionized water were mixed evenly, and then 100 parts of polyurethane, 3 parts of methanol and 8 parts of modified hydroxyethyl cellulose were added and stirred for 6 hours to obtain a coating.
[0062] Step S1: in parts by weight, 20 parts of ethyl orthosilicate, 10 parts of paraffin, 24 parts of anhydrous ethanol and 24 parts of deionized water are mixed evenly, stirred at 48° C. for 20 min, the pH is adjusted to 4.8 with hydrochloric acid and stirred for 4 h, then 30 parts of a magnesium chloride solution with a molar concentration of 0.3 mol / L is added, stirred at 60° C. for 4 h, and then ammonia water is added dropwise to adjust the pH to 7.8 and stirred for 2 h to obtain a modified silica sol;
[0063] Step S2: adding 6 parts of sodium hydroxide to 100 parts of the modified silica sol by weight, stirring at 80° C. for 60 minutes, then adding 6 parts of methyl cellulose (4 parts of carboxymethyl cellulose and 2 parts of hydroxypropyl methyl cellulose) and 3 parts of boron quantum dot-modified titanium dioxide and continuing to stir for 40 minutes to obtain an impregnation solution;
[0064] Step S3: immersing the corrugated core paper in the impregnation liquid at 60° C. for 20 seconds, and then drying it in a constant temperature blast drying oven at 60° C. for 50 minutes to obtain the impregnated corrugated core paper;
[0065] Step S4: Use coating to coat the impregnated corrugated paper (coating amount is 50 g / m 2 ), after the coating treatment is completed, it is first allowed to stand at room temperature for 20 minutes, then cured at 104°C for 70 minutes, and finally processed by corrugated rollers to obtain high-strength and water-resistant corrugated paper.
[0066] Example 2
[0067] This embodiment provides a high-strength and water-resistant corrugated paper, which includes a corrugated core paper and a functional coating coated on the surface of the corrugated core paper, wherein the corrugated core paper is treated by impregnation with an impregnation liquid for modification;
[0068] The corrugated paper is made by the following steps:
[0069] Preparation of boron quantum dot-modified titanium dioxide: (1) In parts by weight, 2 parts of ammonium pentaborate and 1 part of boric acid were added to 20 parts of deionized water and stirred for 1 hour. The mixture was placed in an argon atmosphere for hydrothermal reaction (reaction temperature was 180°C and reaction time was 12 hours). After the reaction was completed, the mixture was cooled to room temperature, 1 part of hydrazine hydrate was added and stirred for 1 hour, and then the supernatant was obtained by centrifugation and freeze-dried to obtain boron quantum dots. (2) In parts by weight, 60 parts of anhydrous ethanol, 20 parts of deionized water, 2 parts of boron quantum dots and 8 parts of 30% hydrochloric acid solution were mixed and stirred for 10 minutes to obtain liquid A; 60 parts of tetrabutyl titanate were added to 90 parts of anhydrous ethanol and stirred for 20 minutes, and then the pH was adjusted to 3.2 with 30% hydrochloric acid solution and stirred for 15 minutes to obtain liquid B; 80 parts of the liquid A were added to 100 parts of the liquid B and stirred for 40 minutes, and then 20 parts of deionized water were added and stirred for 2 hours to form a gel, which was allowed to stand at room temperature for 10 hours, and then dried at 70°C for 22 hours, transferred to a tubular furnace and calcined at 480°C for 4 hours, and cooled to room temperature to obtain boron quantum dot-modified titanium dioxide.
[0070] Preparation of coating: (1) In parts by weight, 20 parts of hydroxyethyl cellulose I (viscosity of 1100 mPa.s) are added to 100 parts of deionized water, stirred for 1 hour under a nitrogen atmosphere, 6 parts of cerium ammonium nitrate and 10 parts of [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl)ammonium hydroxide are added at 36°C, the pH is adjusted to 7.2, and the reaction is carried out for 4 hours. After the reaction is completed, precipitation and separation are carried out with acetone to obtain a precipitate; 36 parts of 2-acrylamido-2-methylpropanesulfonic acid and 10 parts of sodium chloride are added to 200 parts of deionized water and stirred for 30 minutes, and then 40 parts of dimethyldiallylammonium chloride and 20 parts of the above precipitate are added and stirred for 1 hour to obtain a mixed solution, the mixed solution is transferred to a reactor, and 2 parts of potassium persulfate are added at 80°C under a nitrogen atmosphere for reaction for 8 hours. After the reaction is completed, the mixture is cooled to room temperature, dried, and crushed to obtain modified hydroxyethyl cellulose. (2) By weight, 4 parts of acetic acid and 60 parts of deionized water were mixed evenly, and then 90 parts of polyurethane, 1 part of methanol and 4 parts of modified hydroxyethyl cellulose were added and stirred for 4 hours to obtain a coating.
[0071] Step S1: In parts by weight, 10 parts of ethyl orthosilicate, 6 parts of paraffin, 20 parts of anhydrous ethanol and 20 parts of deionized water are mixed evenly, stirred at 46° C. for 30 minutes, the pH is adjusted to 4.2 with hydrochloric acid and stirred for 2 hours, then 20 parts of a magnesium chloride solution with a molar concentration of 0.1 mol / L is added, stirred at 54° C. for 6 hours, and then ammonia water is added dropwise to adjust the pH to 7.4 and stirred for 1 hour to obtain a modified silica sol;
[0072] Step S2: adding 4 parts of sodium hydroxide to 90 parts of the modified silica sol by weight, stirring at 70° C. for 60 minutes, then adding 4 parts of methyl cellulose (2 parts of carboxymethyl cellulose and 2 parts of hydroxypropyl methyl cellulose) and 1 part of boron quantum dot-modified titanium dioxide and continuing to stir for 30 minutes to obtain an impregnation solution;
[0073] Step S3: immersing the corrugated core paper in the impregnation liquid at 50° C. for 20 seconds, and then drying it in a constant temperature blast drying oven at 56° C. for 60 minutes to obtain the impregnated corrugated core paper;
[0074] Step S4: Use coating to coat the impregnated corrugated paper (coating amount is 40 g / m 2 ), after the coating treatment is completed, it is first allowed to stand at room temperature for 10 minutes, then cured at 100°C for 80 minutes, and finally processed by corrugated rollers to obtain high-strength and water-resistant corrugated paper.
[0075] Example 3
[0076] This embodiment provides a high-strength and water-resistant corrugated paper, which includes a corrugated core paper and a functional coating coated on the surface of the corrugated core paper, wherein the corrugated core paper is treated by impregnation with an impregnation liquid for modification;
[0077] The corrugated paper is made by the following steps:
[0078] Preparation of boron quantum dot-modified titanium dioxide: (1) In parts by weight, 3 parts of ammonium pentaborate and 1 part of boric acid were added to 22 parts of deionized water and stirred for 1 hour. The mixture was placed in an argon atmosphere for hydrothermal reaction (reaction temperature was 185°C and reaction time was 11 hours). After the reaction was completed, the mixture was cooled to room temperature, 1 part of hydrazine hydrate was added and stirred for 1 hour, and then the supernatant was obtained by centrifugation and freeze-dried to obtain boron quantum dots. (2) In parts by weight, 70 parts of anhydrous ethanol, 30 parts of deionized water, 3 parts of boron quantum dots and 9 parts of 25% hydrochloric acid solution were mixed and stirred for 15 minutes to obtain liquid A; 70 parts of tetrabutyl titanate were added to 95 parts of anhydrous ethanol and stirred for 25 minutes, and then the pH was adjusted to 3.4 with 25% hydrochloric acid solution, and stirred for 20 minutes to obtain liquid B; 90 parts of the liquid A were added to 110 parts of the liquid B and stirred for 50 minutes, and then 30 parts of deionized water were added and stirred for 3 hours to form a gel, which was allowed to stand at room temperature for 11 hours, and then dried at 75°C for 21 hours, transferred to a tubular furnace and calcined at 490°C for 3 hours, and cooled to room temperature to obtain boron quantum dot-modified titanium dioxide.
[0079] Preparation of coating: (1) In parts by weight, 22 parts of hydroxyethyl cellulose I (viscosity of 1100 mPa.s) are added to 105 parts of deionized water, stirred for 2 hours under a nitrogen atmosphere, and 7 parts of cerium ammonium nitrate and 12 parts of [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl) ammonium hydroxide are added at 38°C, the pH is adjusted to 7.3, and the reaction is carried out for 5 hours. After the reaction is completed, precipitation and separation are carried out with acetone to obtain a precipitate; 38 parts of 2-acrylamido-2-methylpropanesulfonic acid and 12 parts of sodium chloride are added to 210 parts of deionized water and stirred for 35 minutes, and then 42 parts of dimethyldiallylammonium chloride and 25 parts of the above precipitate are added and stirred for 2 hours to obtain a mixed solution, which is transferred to a reactor, and 3 parts of potassium persulfate are added at 82°C under a nitrogen atmosphere for reaction for 7 hours. After the reaction is completed, the mixture is cooled to room temperature, dried, and crushed to obtain modified hydroxyethyl cellulose. (2) By weight, 5 parts of acetic acid and 65 parts of deionized water were mixed evenly, and then 95 parts of polyurethane, 2 parts of methanol and 6 parts of modified hydroxyethyl cellulose were added and stirred for 5 hours to obtain a coating.
[0080] Step S1: in parts by weight, 15 parts of ethyl orthosilicate, 8 parts of paraffin, 22 parts of anhydrous ethanol and 22 parts of deionized water are mixed evenly, stirred at 47° C. for 25 minutes, the pH is adjusted to 4.5 with hydrochloric acid and stirred for 3 hours, then 25 parts of a magnesium chloride solution with a molar concentration of 0.2 mol / L is added, stirred at 58° C. for 5 hours, and then ammonia water is added dropwise to adjust the pH to 7.6 and stirred for 1 hour to obtain a modified silica sol;
[0081] Step S2: adding 5 parts of sodium hydroxide to 95 parts of the modified silica sol by weight, stirring at 75° C. for 55 minutes, then adding 5 parts of methyl cellulose (3 parts of carboxymethyl cellulose and 2 parts of hydroxypropyl methyl cellulose) and 2 parts of boron quantum dot-modified titanium dioxide and continuing to stir for 35 minutes to obtain an impregnation solution;
[0082] Step S3: immersing the corrugated core paper in the impregnation liquid at 55° C. for 15 seconds, and then drying it in a constant temperature forced air drying oven at 58° C. for 55 minutes to obtain the impregnated corrugated core paper;
[0083] Step S4: Use coating to coat the impregnated corrugated paper (coating amount is 45 g / m 2 ), after the coating treatment is completed, it is first allowed to stand at room temperature for 15 minutes, then cured at 102°C for 75 minutes, and finally processed by corrugated rollers to obtain high-strength and water-resistant corrugated paper.
[0084] Comparative Example 1
[0085] The difference between this comparative example and Example 1 is that commercially available silica sol (item number sy07, purchased from Qingdao Shuoyuan Silica Gel Technology Co., Ltd.) is used instead of the modified silica sol.
[0086] Comparative Example 2
[0087] The difference between this comparative example and Example 1 is that the amount of carboxymethyl cellulose in the impregnation solution is changed to 5 parts, and the amount of hydroxypropyl methyl cellulose is changed to 1 part.
[0088] Comparative Example 3
[0089] The difference between this comparative example and Example 1 is that the amount of carboxymethyl cellulose in the impregnation solution is changed to 2 parts, and the amount of hydroxypropyl methyl cellulose is changed to 4 parts.
[0090] Comparative Example 4
[0091] The difference between this comparative example and Example 1 is that commercially available titanium dioxide (CAS No. 13463-67-7, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.) is used instead of boron quantum dot-modified titanium dioxide.
[0092] Comparative Example 5
[0093] The difference between this comparative example and Example 1 is that hydroxyethyl cellulose I is used instead of modified hydroxyethyl cellulose.
[0094] Comparative Example 6
[0095] The difference between this comparative example and Example 1 is that hydroxyethyl cellulose II is used instead of hydroxyethyl cellulose I to prepare the modified hydroxyethyl cellulose.
[0096] Comparative Example 7
[0097] The difference between this comparative example and Example 1 is that hydroxyethyl cellulose III is used instead of hydroxyethyl cellulose I to prepare the modified hydroxyethyl cellulose.
[0098] Performance Testing
[0099] The corrugated paper of the above embodiment and comparative example was subjected to the following tests:
[0100] (1) Edge compression strength test
[0101] The edge compression strength is tested according to the requirements of GB / T 2679.17-1997 Determination of edge compression strength of corrugated board (edge reinforcement method).
[0102] (2) Oxygen index test
[0103] The oxygen index is tested with reference to the requirements of GB / T 5454-1997 Textiles Burning Performance Test - Oxygen Index Method.
[0104] (3) Water absorption test
[0105] The water absorption is tested according to the requirements of GB / T 461.3-2005 Determination of water absorption of paper and paperboard (immersion method).
[0106] The test results are shown in Table 1.
[0107] Table 1 Performance test results
[0108] Edge compression strength (kN / m) Oxygen Index (LOI) <![CDATA[Water absorption (g / m 2 )]]> Example 1 7.46 32.9 4.85 Example 2 7.28 32.2 4.93 Example 3 7.35 32.6 4.89 Comparative Example 1 5.19 24.3 8.63 Comparative Example 2 6.54 27.8 6.27 Comparative Example 3 6.61 28.4 6.21 Comparative Example 4 5.32 25.1 8.45 Comparative Example 5 5.25 24.7 8.56 Comparative Example 6 6.73 29.2 6.08 Comparative Example 7 6.68 28.9 6.13
[0109] From the above performance test results, it can be seen that the corrugated paper of Example 1-2 has the best comprehensive effect, with an edge compression strength of 7.28-7.46 kN / m, an oxygen index (LOI) of 32.2-32.9, and a water absorption of 4.85-4.93 g / m 2 This is mainly because it uses impregnation liquid and coating to comprehensively treat the corrugated core paper, and uses modified silica sol and boron quantum dot-modified titanium dioxide in the impregnation liquid, while modifying the hydroxyethyl cellulose in the coating, which significantly increases the edge compression strength, improves the oxygen index, and effectively reduces water absorption.
[0110] However, the comparative example did not adopt the necessary technical scheme, resulting in that its corresponding performance tests were significantly worse than those of the embodiments. Compared with Example 1, Comparative Example 1 used commercially available silica sol instead of modified silica sol, so the edge compression strength was reduced, the oxygen index was reduced, and the water absorption was increased; compared with Example 1, the amount of carboxymethyl cellulose in the impregnation solution of Comparative Example 2 was changed to 5 parts, and the amount of hydroxypropyl methylcellulose was changed to 1 part. The amount of carboxymethyl cellulose was too much, and the compounding effect was not good, so the edge compression strength was reduced, the oxygen index was reduced, and the water absorption was increased; compared with Example 1, the amount of carboxymethyl cellulose in the impregnation solution of Comparative Example 3 was changed to 2 parts, and the amount of hydroxypropyl methylcellulose was changed to 4 parts. The amount of carboxymethyl cellulose was too little, and the compounding effect was not good, so the edge compression strength was reduced, the oxygen index was reduced, and the water absorption was increased; compared with Example 1 In comparative example 4, commercially available titanium dioxide is used to replace boron quantum dot modified titanium dioxide, and the edge compression strength is reduced, the oxygen index is reduced, and the water absorption is increased; compared with Example 1, comparative example 5 uses hydroxyethyl cellulose I to replace modified hydroxyethyl cellulose, and the edge compression strength is reduced, the oxygen index is reduced, and the water absorption is increased; compared with Example 1, comparative example 6 uses hydroxyethyl cellulose II to replace hydroxyethyl cellulose I to prepare modified hydroxyethyl cellulose. Since the viscosity of hydroxyethyl cellulose II is too small, the modification effect is not good, the edge compression strength is reduced, the oxygen index is reduced, and the water absorption is increased; compared with Example 1, comparative example 7 uses hydroxyethyl cellulose III to replace hydroxyethyl cellulose I to prepare modified hydroxyethyl cellulose. Since the viscosity of hydroxyethyl cellulose III is too large, the modification effect is not good, the edge compression strength is reduced, the oxygen index is reduced, and the water absorption is increased. The above experimental results further prove the importance of the technical scheme defined in the present invention for its technical effect.
[0111] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A high-strength water-resistant corrugated paper, characterized in that: The high-strength water-resistant corrugated paper comprises corrugated core paper and a functional coating coated on the surface of the corrugated core paper, wherein the corrugated core paper is treated by impregnation and modification with an impregnation liquid; The corrugated paper is made by the following steps: Step S1: in parts by weight, 10 to 20 parts of ethyl orthosilicate, 6 to 10 parts of paraffin, 20 to 24 parts of anhydrous ethanol and 20 to 24 parts of deionized water are mixed uniformly, stirred at 46 to 48° C. for 20 to 30 minutes, the pH is adjusted to 4.2 to 4.8 with hydrochloric acid and stirred for 2 to 4 hours, then 20 to 30 parts of a magnesium chloride solution with a molar concentration of 0.1 to 0.3 mol / L is added, stirred at 54 to 60° C. for 4 to 6 hours, and then ammonia water is added dropwise to adjust the pH to 7.4 to 7.8 and stirred for 1 to 2 hours to obtain a modified silica sol; Step S2: adding 4 to 6 parts of sodium hydroxide to 90 to 100 parts of the modified silica sol by weight, stirring at 70 to 80° C. for 50 to 60 minutes, then adding 4 to 6 parts of methyl cellulose and 1 to 3 parts of titanium dioxide and continuing to stir for 30 to 40 minutes to obtain an impregnation solution; Step S3: immersing the corrugated core paper in the impregnation liquid at 50-60° C. for 10-20 seconds, and then drying it in a constant temperature blast drying oven at 56-60° C. for 50-60 minutes to obtain the impregnated corrugated core paper; Step S4: coating the impregnated corrugated paper with a coating, and after the coating is completed, first standing at room temperature for 10 to 20 minutes, then curing at 100 to 104° C. for 70 to 80 minutes, and finally processing with a corrugated roller to obtain high-strength and water-resistant corrugated paper.
2. The high-strength water-resistant corrugated paper according to claim 1, characterized in that: The methyl cellulose is carboxymethyl cellulose and hydroxypropyl methyl cellulose; the mass ratio of the carboxymethyl cellulose to the hydroxypropyl methyl cellulose is (1-2):
1.
3. The high-strength water-resistant corrugated paper according to claim 1, characterized in that: The titanium dioxide is boron quantum dot modified titanium dioxide; The preparation method of boron quantum dot modified titanium dioxide comprises: mixing 60 to 80 parts of anhydrous ethanol, 20 to 40 parts of deionized water, 2 to 4 parts of boron quantum dots and 8 to 10 parts of hydrochloric acid solution with a mass concentration of 20 to 30% for 10 to 20 minutes to obtain liquid A; adding 60 to 80 parts of tetrabutyl titanate to 90 to 100 parts of anhydrous ethanol and stirring for 20 to 30 minutes, and then adjusting the pH to 3 with a hydrochloric acid solution with a mass concentration of 20 to 30%. .2~3.6, stir for 15~30min to obtain liquid B; add 80~100 parts of the liquid A to 100~120 parts of the liquid B and stir for 40~60min, then add 20~40 parts of deionized water and stir for 2~4h to form a gel, let it stand at room temperature for 10~12h, then dry at 70~80℃ for 20~22h, transfer to a tubular furnace and calcine at 480~500℃ for 2~4h, and cool to room temperature to obtain boron quantum dot modified titanium dioxide.
4. The high-strength water-resistant corrugated paper according to claim 3, characterized in that: The preparation method of boron quantum dots comprises: adding 2 to 4 parts of ammonium pentaborate and 1 to 2 parts of boric acid to 20 to 25 parts of deionized water by weight, stirring for 1 to 2 hours, placing in an argon atmosphere for hydrothermal reaction, cooling to room temperature after the reaction is completed, adding 1 to 2 parts of hydrazine hydrate and stirring for 1 to 2 hours, then centrifuging to obtain a supernatant, and freeze-drying to obtain boron quantum dots.
5. The high-strength water-resistant corrugated paper according to claim 4, characterized in that: The reaction temperature of the hydrothermal reaction is 180-190° C., and the reaction time is 10-12 hours.
6. The high-strength water-resistant corrugated paper according to claim 1, characterized in that: The coating preparation method comprises: mixing 4-6 parts of acetic acid and 60-70 parts of deionized water uniformly by weight, then adding 90-100 parts of polyurethane, 1-3 parts of methanol and 4-8 parts of hydroxyethyl cellulose and stirring for 4-6 hours to obtain the coating.
7. The high-strength water-resistant corrugated paper according to claim 6, characterized in that: The hydroxyethyl cellulose is modified hydroxyethyl cellulose; The preparation method of the modified hydroxyethyl cellulose comprises: adding 20 to 24 parts of hydroxyethyl cellulose to 100 to 110 parts of deionized water by weight, stirring for 1 to 3 hours under a nitrogen atmosphere, adding 6 to 8 parts of cerium ammonium nitrate and 10 to 14 parts of [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl)ammonium hydroxide at 36 to 40° C., adjusting the pH to 7.2 to 7.4, reacting for 4 to 6 hours, and after the reaction is completed, precipitating and separating with acetone to obtain a precipitate; adding 36 to 4 0 parts of 2-acrylamido-2-methylpropanesulfonic acid and 10-14 parts of sodium chloride are added to 200-220 parts of deionized water and stirred for 30-40 minutes, then 40-45 parts of dimethyldiallylammonium chloride and 20-30 parts of the above precipitate are added, and stirred for 1-3 hours to obtain a mixed solution, and the mixed solution is transferred to a reaction kettle, and under the protection of a nitrogen atmosphere, 2-4 parts of potassium persulfate are added at 80-84° C. to react for 6-8 hours. After the reaction is completed, it is cooled to room temperature, dried, and crushed to obtain modified hydroxyethyl cellulose.
8. The high-strength water-resistant corrugated paper according to claim 7, characterized in that: The viscosity of the hydroxyethyl cellulose is 800-1200 mPa.s.
9. The high-strength water-resistant corrugated paper according to claim 1, characterized in that: The coating amount in the coating process is 40 to 50 g / m 2 .
10. Use of the high-strength water-resistant corrugated paper as claimed in any one of claims 1 to 9 in waterproof cartons.
Citation Information
Patent Citations
Preparation process of high-strength waterproof composite corrugated paper
CN117661366A
Catalyst for special polyolefin diaphragm production material, and preparation method and application thereof
CN107903344A
Production process of multi-layer corrugated board
CN116080153A
High-strength corrugated composite paperboard and processing technology thereof
CN116100912A
Reinforced composition for corrugated board sheet and corrugated board using the same
KR1020130043473A